Impacto de los recursos didácticos en el proceso de enseñanza-aprendizaje de la asignatura de computación para el segundo grado de la escuela de educación básica “GENERAL RUMIÑAHUI” del cantón Yantzaza, provincia de Zamora Chinchipe, periodo 2013 – 2014. Lineamientos alternativos - Chimbo Yaure, Alexandra Elizabeth (2015)
This thesis refers to: IMPACT OF TEACHING RESOURCES IN THE PROCESS OF LEARNING COMPUTER COURSE FOR THE SECOND GRADE SCHOOL OF BASIC EDUCATION "GENERAL RUMIÑAHUI" CANTON YANTZAZA, PROVINCE OF ZAMORA CHINCHIPE, PERIOD 2013 - GUIDELINES ALTERNATIVE 2014, performed according to what stable Academic Regulation Regime of the National University of Loja. The methods used for the preparation of this research work were: Scientific, Inductive - Deductive Model Statistically, the same that served effectively help to achieve the proposed goal. The techniques and instruments used were: The Direct Observation applied to second grade students of the School of Basic Education "General Rumiñahui" to establish whether the teaching resources used in the daily work, for which a model was used Record previously established observation, and interview teachers, to determine the impact of teaching resources in the teaching - learning process in the classroom activities. It is concluded that: 100% of teachers surveyed say they use educational resources such as books, pamphlets, computers, audiovisual, internet, working hours, and 100% of teachers said that activities like is performed: designs, practical work, graphs, charts, tables with the purpose of making use of teaching resources and arouse students' creativity. Regarding the observation guide students applied to evaluate the use of teaching resources in the teaching-learning process in the course of computation, the results determine that: 90% of students about being comfortable with the use the teacher makes learning resources available, since they have generated significant learning in students.